Comparison of resting-state brain activity between insomnia and generalized anxiety disorder: A coordinate-based meta-analysis - Tongfei Jiang; Xuejiao Yin; Liying Zhu; Guiling Wang; Fan Zhang; Jing Guo (Brain Imaging and Behavior, 2024)

First record of the sap beetle Phenolia picta invading Eastern honey bee (Apis cerana) (Hymenoptera, Apidae) colonies - Lin Du; Wenbin Liu; Xiaoshun Chen; Jinge Licao; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

High variation of worker cell and morphology between two adjacent populations of honey bee, Apis cerana (Hymenoptera, Apidae) - Rui Zhu; Weilai Zhong; Yuhui Chen; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

Absorption and utilization of polysaccharides from Cordyceps militaris fruiting bodies and their protective effects against CCl4-induced acute liver injury in mice - Lin Lan; Jingxin Wang; Hao Luo; Min Cao; Nianhong Guo; Guiling Fan; Shengyu Wang; Zaixing Sun; QiaoLing He; Yufeng Li (Food Bioscience, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

A New Method for Detection African Swine Fever Virus: Time-resolved Fluorescence Immunoassay - Cuicui Chen; Hongrui Lai; Huankun Liang; Ying He; Guiling Guo; Laiqing Li (Journal of Fluorescence, 2021)

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

Impact of histaminergic H3 receptor antagonist on hypoglossal nucleus in chronic intermittent hypoxia conditions - Liang Xie; Qinhan Wu; Weiping Hu; Xu Wu; Guiling Xiang; Shengyu Hao; Han Guo; Shanqun Li (Psychopharmacology, 2021)

Identification of porcine CTLA4 gene polymorphism and their association with piglet diarrhea and performance traits - Xiaowen Gao; Dongchun Guo; Mingxing Kou; Guiling Xing; Andong Zha; Xiuqin Yang; Xibiao Wang; Shengwei Di; Jiancheng Cai; Buyue Niu (Molecular Biology Reports, 2019)

Influence of a water regulation event on the age of Yellow River water in the Bohai - Zhen Li; Haiyan Wang; Xinyu Guo; Zhe Liu; Huiwang Gao; Guiling Zhang (Journal of Ocean University of China, 2017)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)